Effect of different pineapple juice (Ananas Comosus L.) preparations on the microstructure, staling and textural properties of wheat bread. - Olusegun, Lasekan; Chiemela, Chinma; Ossai, Beatrice; Mohd Adzahan, Noranizan (Wiley-Blackwell, 2011)
The effect of adding different pineapple juice preparations on the microstructure, staling and textural properties of wheat bread were investigated. The loaves quality, crust and crumb color, and staling profile (crumb firmness, enthalpy) during storage were monitored. The micro-structural differences of crumbs were also examined using microtome and Scanning Electron Microscopy (SEM). Results revealed that the specific volume of fresh loaves baked with concentrated pineapple juice (PJC) bread was not significantly (P = 0.05) different from that of control wheat bread (WB). Likewise, firmness of crumbs, number of crumb cells, area air cell, bake loss, volume yield, and crust and crumb color of the freshly baked PJC bread were not significantly (P = 0.05) different from the control WB. However, during storage, the retrogradation of starch in pineapple bread crumbs (PJC and pineapple juice [PJ] bread) was significantly (P = 0.05) retarded as compared with the control WB. While there was no significant (P = 0.05) textural differences between the crumbs of freshly produced PJC bread and the crumb of the control WB, staled breads revealed significant textural changes in their crumbs. Microtome and SEM revealed the presence of many starch granules on the surface of pore walls in the control WB, whereas the PJC bread contained starch gels cemented between starch granules. Gluten nets were found to be uniform and more oriented in the control WB than in the PJC bread. However, same gluten nets were dense and non-uniform in the PJ bread.